Allyl and Benzyl Modified Aramid Nanofibers as an Enhancement in Polystyrene-Based Composites - Peng, Guo; Yaoqin, Wu; Congcong, Dong; Changmei, Sun; Rongjun, Qu; Chunnuan, Ji; Ying, Zhang; Ying, Wang (Frontiers in Chemistry, 2020)
Aramid nanofibers (ANFs) represent the most promising nanoscale building blocks for high-performance nanocomposites. But their applications are mostly limited to those polymers containing –OH or –NH2 groups that can interact with ANFs through hydrogen bonding or others. In this paper, allyl and benzyl modified ANFs were successfully fabricated using a metallization method followed by functionalization with allyl and benzyl bromide. A series of modified aramid nanomaterials (ANMs) with different degrees of modification were prepared and their morphologies studied. The modified ANFs were added to polystyrene (PS) films as reinforcements. The mechanical properties of the resulting composite PS films including Young’s modulus, toughness and yield strength were dramatically improved compared to those of pure PS film. These new types of reinforcement additives for nonpolar polymer materials are presented in this paper.